Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Nasabah BPRS Mandiri Mitra Sukses Gresik - Fataruba, Susanto; Maulana, Alfin (Journal of Islamic Economics Studies and Practices, 2023)
This study was conducted to test whether the implementation of Service and Facility Quality has an influence on BPRS Mandiri Mitra Sukses Gresik Customer Satisfaction. The research data used is primary data obtained through questionnaires to BPRS Mandiri Mitra Sukses Gresik customers. The data obtained were analyzed using multiple regression quantitative analysis methods using the SmartPLS v. 3 program. The results of this study are known that partially the Service Quality variable affects the Customer Satisfaction variable but the Facility variable affects the Customer Satisfaction variable, while simultaneously the two exogenous variables affect the Customer Satisfaction of BPRS Mandiri Mitra Sukses Gresik.